2016
DOI: 10.1007/s00280-015-2948-8
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and pancreatic cancer: Is there a role?

Abstract: Pancreatic cancer is the fourth leading cause of cancer-related deaths in the USA, with a 5-year survival rate of 6 %. Anti-hyperglycemic treatments for type 2 diabetes mellitus that induce hyperinsulinemia (i.e., sulfonylureas) are thought to increase cancer risk, whereas treatments that lower insulin resistance and hyperinsulinemia (i.e., metformin) are considered cancer prevention strategies. Metformin is a cornerstone in the treatment of diabetes mellitus type 2. Retrospective studies have shown a survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 64 publications
1
34
1
Order By: Relevance
“…As the potential role of anti-diabetic drugs (metformin and insulin) in influencing pancreatic carcinogenesis has been reported (De Souza et al 2016), we also specifically investigated the role of such drugs in our multinational cohort. Although the prevalent use of insulin alone was more frequent among cases than in controls (4.1% vs 1.6%), this difference was not significant as the study was underpowered to assess it.…”
Section: Discussionmentioning
confidence: 99%
“…As the potential role of anti-diabetic drugs (metformin and insulin) in influencing pancreatic carcinogenesis has been reported (De Souza et al 2016), we also specifically investigated the role of such drugs in our multinational cohort. Although the prevalent use of insulin alone was more frequent among cases than in controls (4.1% vs 1.6%), this difference was not significant as the study was underpowered to assess it.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing consensus that diabetes is a potential cause of pancreatic cancer [10]. Currently, chemotherapy serves as a main supplementation when necessary subsequent to surgery for pancreatic cancer patients at an early stage as well as the primary therapeutic regimen for advanced pancreatic cancer, achieving remarkable benefit, however with evident increase in deleterious effects in relation to the nonspecific damage at the meantime [8].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggested a preventive role of the well-known anti-diabetic drug metformin accompanied with chemotherapy and radiotherapy in the malignance of cancer cell by inhibiting cell division, promoting apoptosis and autophagy, down-regulating circulating insulin, activating the immune system and crippling irradiation-resistance [8][9][10]. The preventive role of metformin was shown in multiple cancer types, including pancreatic, colorectal, prostate, and hepatocellular carcinoma, resulting in decreased cancer incidence and mortality [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have shown a survival benefit in diabetic patients with pancreatic cancer that have been treated with metformin compared with patients treated with insulin or sulfonylureas. [32,33] However, there is limitation on applying registry data to elucidate the association between medication history and the occurrence of pancreatic cancer. Further study should be conducted to specifically deal with this interesting topic.…”
Section: Discussionmentioning
confidence: 99%